Pelatihan Menulis Karya Ilmiah Pada Era Digitalisasi : Analisis Kemampuan Siswa Di Man 1 Tanjung Pura - Mhd. Fuad Zaini Siregar, Muhammad Riski Syahputra, Ardi Bancin (Pusdikra Publishing, 2023)
The activity of scientific writing training at MAN 1 Tanjung Pura is a form of community service, considering the importance of soft skills in writing various scientific works today. The method used is face-to-face training with stages of opening, motivation, materials, and evaluation. The training in scientific writing in the era of digitalization encourages students to be actively engaged in writing activities. The objective of this training is to provide the necessary skills and knowledge for students to write scientific works effectively. During this training, students are taught various types of scientific works and how to access and evaluate information sources through digital technology. The use of software and applications is also introduced to assist students in composing, organizing, and publishing scientific works digitally.